2018
DOI: 10.1111/jcmm.13628
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 attenuates inflammatory response in COPD/emphysema: Crosstalk with Wnt3a/β‐catenin and AMPK pathways

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by persistent airflow limitation and abnormal inflammatory response. Wnt/β‐catenin and AMP‐activated protein kinase (AMPK) have been shown to modulate lung inflammatory responses and injury. However, it remains elusive whether Wnt/β‐catenin and AMPK modulate nuclear factor erythroid‐2 related factor‐2 (Nrf2)‐mediated protective responses during the development of emphysema. Here we showed that treatment with a Wnt pathway activator (LiCl) reduced el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 43 publications
(99 reference statements)
3
78
0
Order By: Relevance
“…35 Previous studies have indicated the TGF-β 1 signals-Smad2, β-catenin signalling axis activate EMT and α-SMA. 11,36 To explore the mechanism, the underlying TSPAN1-mediated the EMT in lung epithelial cells, we further assumed that the action of TSPAN1 on EMT is involved in activating Smad2/3 and the beta-catenin pathway, as shown in Figure 5, knockdown TSPAN1 promoted the phosphorylation of Smad2/3, but reduced the accumulation of beta-catenin ( Figure 5A,D), indicating the TM protein has a different action for profibrosis signalling pathways, even opposite action based on the TSPAN1 alone or combined with other proteins and the exogenous expression of TSPAN1-blocked TGF-β 1 -induced the phosphorylation of Smad2/3 and the accumulation of beta-catenin in A549 and ATII cells ( Figure 5F-I). These results showed that TSPAN1 modulated the TGF-β/Smad2/3 and beta-catenin signalling pathway in A549 and ATII cells.…”
Section: Discussionmentioning
confidence: 99%
“…35 Previous studies have indicated the TGF-β 1 signals-Smad2, β-catenin signalling axis activate EMT and α-SMA. 11,36 To explore the mechanism, the underlying TSPAN1-mediated the EMT in lung epithelial cells, we further assumed that the action of TSPAN1 on EMT is involved in activating Smad2/3 and the beta-catenin pathway, as shown in Figure 5, knockdown TSPAN1 promoted the phosphorylation of Smad2/3, but reduced the accumulation of beta-catenin ( Figure 5A,D), indicating the TM protein has a different action for profibrosis signalling pathways, even opposite action based on the TSPAN1 alone or combined with other proteins and the exogenous expression of TSPAN1-blocked TGF-β 1 -induced the phosphorylation of Smad2/3 and the accumulation of beta-catenin in A549 and ATII cells ( Figure 5F-I). These results showed that TSPAN1 modulated the TGF-β/Smad2/3 and beta-catenin signalling pathway in A549 and ATII cells.…”
Section: Discussionmentioning
confidence: 99%
“…24 SIAH2 upregulation mediates the ubiquitination of NRF2 which has been previously associated with respiratory function 25 and COPD. 26 Functional annotation of differently methylated genes identified enrichment of the molecular function alternative splicing (appendix p43). This finding is consistent with earlier reports that genes associated with COPD (unlike those associated with other complex traits examined) have greater transcriptional complexity due to a disproportionately high level of alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not currently study the impact of coadministration of PI3Kd inhibitors with other respiratory drugs, we believe that target engagement experiments (such as presented in this work) can be the basis of future explorations. From our point of view, this can be expanded to potential novel respiratory targets such as NOX4 and Nrf2 (Zhao et al, 2015;Zhou et al, 2016;Cui et al, 2018).…”
Section: Downloaded Frommentioning
confidence: 99%